SUZUKI MOTORCYCLE MARKETING STRATEGY THROUGH SALES PROMOTION AT PT SINAR GALESONG MANDIRI BRANCH URIP SUMOHARJO MAKASSAR - Syam, Shofiana; Rachman, Siswati (Jurnal Ekonomi Balance, 2019)
This research aims to know the Suzuki Motorcycle Strategies and Constraints in Conductiong Sales Promotion at PT Sinar Galesong Mandiri Branch Urip Sumoharjo Makassar. The method used was descriptive qualitative which the author described the results of the observation and analyzed the data obtained in the field. Research the result of the research was conducted from April 15 to May 14, 2019. The result showed that there were four strategies used in PT Sinar Galesong Mandiri Branch Urip Sumoharjo Makassar, they are, Advertising, Personal Sales, Sales Promotion and Publicity. Those strategies had been going well, although there were still some obstacles, such as The Lack of consumer interest in Suzuki Motorcycles, The Lack of communication with consumer, The High level of competition, Uncertainty from consumers, The Lack of variation in product units, Installment deductions which only two times compared to other competitors. Thus, the strategy needs to be maintained and improved so that there will be no more obstacles that will occur during the promotion.